Sale of goods and sale of debts: a comparative analysis - Saiti, Buerhan; Abdullah , Adam (IIUM, 2015)
Islam clearly identifies not only lawful (halal) activities, but also unlawful (haram) activities as well. Differences of opinion may arise in these two areas too. In order to achieve the ultimate in Islam, we should exercise caution when practicing Islamic finance. In Islamic banking and finance, most of the contracts deal with exchange contracts (al-muawadat) that are essentially trading-based activities. Whereas, conventional banking and finance mainly deals with only one contract involving lending and borrowing activities. Settlement of price consideration can be made on the spot (cash) and on a deferred payment basis (credit sale). However, the credit sale has resulted in a lack of consensus (ijma) amongst jurists regarding the validity of selling a debt to a third party. Injustices (zulm), uncertainty (gharar) and usury (riba) are typically the reasons cited by the jurists in order to support their opinions. This paper will look into the validity of the sale of goods and debt, as well as, the problems associated with these two kinds of sale